Cassava: fuel of the future? - International Center for Tropical Agriculture (2009)
A documentary about the successful trial of cassava biofuel. The initiative brings together CIAT's high-starch cassava varieties with Clayuca's small-scale processing plant to produce eco-efficient fuel for a variety of purposes.